On the importance of monitoring Economic Partnership Agreements : principles and concrete steps for the negotiations and beyond (ECDPM MaastrichtNL, 2008)
Answers four questions that ask the reason why EPAs should be monitored. Makes recommendations that sugest options for the inclusion of provisions in the text of EPAs.
Keywords: TRADE NEGOTIATIONS